Conflitos agrários e direito: a luta pela terra e a perspectiva do pluralismo jurídico - Machado, Roniery Rodrigues (2017)
Interface's study between state law and agrarian conflicts Discusses the process by which the peasants work out a conception of law in situations of conflict and operate this design for the constitution of your identity as a social subject. It also discusses the dialogue between this law's constitutions process and the interface with the critical law, in particular, “Law Found on the Street” and “Juridical Pluralism”. The basic problem of this work is, therefore, the land’s right constitution process by the peasants and their relationship with the State, in an interface with the expressed critical law in the formulations of “Law on the Street” and “Juridical Pluralism”. The method used in the research is the dialectical historical materialist critical. The study has as sources a bibliography and documents reflection on the theme, of social movements in which a conception of struggle and law is expressed.